Design of a Task-Based Modular Re-Configurable Agricultural Robot. Issue 16 (2016) - Levin, Mark; Degani, Amir
Abstract: This paper presents a new method for designing an optimal harvesting agriculture manipulator. The novelty in our approach is the re-configurability of the robot's joints, i.e., the ability to assemble a given set of joints in a variable order to form different manipulators for different harvesting tasks. This way, we provide the farmer with the ability to change the robot's construction before each harvesting period to achieve maximal use of the robot throughout the year. The efficiency of task-based optimization is demonstrated on apple and tangerine harvesting tasks. The method is shown to improve efficiency in terms of success harvest ratio and harvest time compared with non-reconfigurable robots of the same complexity.